2019
DOI: 10.1088/2058-6272/ab10a7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nitrogen impurities on the characteristics of a patterned helium dielectric barrier discharge at atmospheric pressure

Abstract: In this paper, a two-dimensional axisymmetric fluid model was established to investigate the influence of nitrogen impurity content on the discharge pattern and the relevant discharge characteristics in an atmosphere pressure helium dielectric barrier discharge (DBD). The results indicated that when the nitrogen content was increased from 1 to 100 ppm, the discharge pattern evolved from a concentric-ring pattern into a uniform pattern, and then returned to the concentricring pattern. In this process, the disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 77 publications
1
20
0
1
Order By: Relevance
“…In the previous studies on He and He/N 2 [4], [16], [23], [37], [38], the influence of n e0 on the evolution of MCP discharges was obvious and thus discussed thoroughly. In this study, however, it is found that n e0 remains basically unchanged when the air content is increased above 500 ppm (namely, in stage II).…”
Section: ) Stage I: 50 Ppm-500 Ppmmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous studies on He and He/N 2 [4], [16], [23], [37], [38], the influence of n e0 on the evolution of MCP discharges was obvious and thus discussed thoroughly. In this study, however, it is found that n e0 remains basically unchanged when the air content is increased above 500 ppm (namely, in stage II).…”
Section: ) Stage I: 50 Ppm-500 Ppmmentioning
confidence: 99%
“…Thus the attachment reaction is one of the important differences between the chemical reactions regarding O 2 and N 2 . In our previous studies about MCP discharges [16], [23], [38], we have neglected the effect of the O 2 impurity, thus certainly without considering the O 2 attachment reaction. As stated earlier in Section III.A, the O 2 attachment reaction will become stronger as the proportion of air content increases.…”
Section: The Effect Of O 2 Attachment Reactionmentioning
confidence: 99%
“…Based on the work of previous researchers, the simulation model in this paper considers the main particles and chemical reactions in the air [28]. The main particles considered are: electrons, N [28,30]. Additionally, the chemical scheme is shown in the Appendix A (Tables A1 and A2).…”
Section: Partial Discharge Numerical Simulation Modelmentioning
confidence: 99%
“…The previous research of our research group shows that in the partial discharge with a similar geometric size, the photoionization reaction will not affect the discharge morphology of partial discharge. Therefore, photoionization is not considered in this paper [27,28].…”
Section: Partial Discharge Numerical Simulation Modelmentioning
confidence: 99%
“…As regards the chemical scheme, we reuse the one that has been previously validated in our 1D and 2D DBD simulations . More specifically, the gas gap is filled with helium and small amounts of nitrogen impurities (100 ppm).…”
Section: Model Descriptionmentioning
confidence: 99%